2020
DOI: 10.1021/jacs.9b12299
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Palladium(0)-Catalyzed Atropo-enantioselective C–H Arylation of Heteroarenes

Abstract: General Methods Experimental Procedures, Reagents and Glassware All commercially available chemicals were used as purchased for the synthesis of substrates. All reactions were carried out under an atmosphere of nitrogen in oven-dried glassware with magnetic stirring, unless otherwise indicated. Acetonitrile (MeCN) was dried over CaH2, distilled and stored inside the N2-filled glovebox. Toluene, THF and dichloromethane were purified by the Innovative Technology Solvent Delivery System. Chemicals were used as ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(65 citation statements)
references
References 96 publications
1
63
0
1
Order By: Relevance
“…The following year, Baudoin and Cramer reported an atroposelective intermolecular Pd‐catalyzed C−H arylation of 1,2,3‐triazoles and pyrazoles . They used a Pd 0 complex with the chiral monodentate phosphine ligand L3 for the arylation of a broad range of triazoles and pyrazoles in high enantioselectivity.…”
Section: Strategies For the Construction Of Multiple‐axis Systemsmentioning
confidence: 99%
“…The following year, Baudoin and Cramer reported an atroposelective intermolecular Pd‐catalyzed C−H arylation of 1,2,3‐triazoles and pyrazoles . They used a Pd 0 complex with the chiral monodentate phosphine ligand L3 for the arylation of a broad range of triazoles and pyrazoles in high enantioselectivity.…”
Section: Strategies For the Construction Of Multiple‐axis Systemsmentioning
confidence: 99%
“…Following the intramolecular C-H arylation described above, Cramer and Baudoin reported in 2020 the more challenging intermolecular atropoenantioselective C-H arylation of electron-deficient heteroarenes. 20 In their initial study, they focused on the synthesis of Ar-HetAr scaffolds via C-H arylation of 1,2,3 triazole derivatives, which are biologically relevant units recognized as bioisosteres and pharmacophores. To achieve a configurational stability of the heterobiaryl axis at 80-100 °C over prolonged reaction times, the coupling between 1-methyl-4-phenyl-1H-1,2,3-triazole and 1-bromo-2-methoxy naphthalene, furnishing a product with four ortho-substituents around the heterobiaryl axis, was selected (Scheme 7).…”
Section: Atropo-enantioselective Intermolecular Pd-catalyzed C-h Arylmentioning
confidence: 99%
“…Thef ollowing year, Baudoin and Cramer reported an atroposelective intermolecular Pd-catalyzed C À Harylation of 1,2,3-triazoles and pyrazoles. [14] They used aPd 0 complex with the chiral monodentate phosphine ligand L3 for the arylation of ab road range of triazoles and pyrazoles in high enantio- selectivity.I nvestigations of the deuterium kinetic isotope effect revealed that the C À Ha ctivation is the rate-determining but not the enantio-determining step.Interestingly,the CÀ Ha rylation of 1,5-dibromo-2,6-dimethoxynaphthalene 10with two equivalents of 1-methyl-4-phenyl-1H-1,2,3-triazole (9)allowed the synthesis of the double-axis heteroatropisomer (M,M)-11 in good yield (76 %) and excellent enantiocontrol (> 99 % ee)w ithout formation of the meso stereoisomer (Scheme 5).…”
Section: Aryl-aryl Cross-coupling (Type Dmolecules)mentioning
confidence: 99%